Respostas

2014-05-27T12:48:59-03:00
[a11 a12]
[a21 a22]

aij = (-1) i + J
a11 = (-1).1 + 1 = 0
a12 = (-1).1 + 2 = 1
a21 = (-1).2 + 1 = -1
a22 = (-1).2 + 2 = 0

[0   1]
[-1  0] 
1 5 1
  • Usuário do Brainly
2014-05-27T12:50:33-03:00
  \left[\begin{array}{ccc}a11&a12&\\a21&a22\\\end{array}\right]

com isso temos:

aij=(-1)1+1
aij=-1+1
aij=0

aij=(-1)1+2
aij=-1+2
aij=1

aij=(-1)2+1
aij=-2+1
aij=-1

aij=(-1)2+2
aij=-2+2
aij=0

substituindo os elementos temos:

  \left[\begin{array}{ccc}0&1&\\-1&0&\\\end{array}\right]